Development of a fuzzy loss-based process capability index - Abdolshah, Mohamad (2010)
Process capability indices are appropriate tools in order to measure the inherent capability of process, but most of these indices cannot take into account the losses of a process such as rejects, while in today’s competitive business environment, it is becoming more and more important for companies to evaluate and minimize their losses. Since most of process capability indices do not consider the losses, the process capability indices based on losses can help manufacturers to understand the real capability of their processes in order to improve them.